The Interaction Model of Qur’an and Science in The Indonesian Ministry of Religious Affairs’ Scientific Tafsir - Muhammad Hadrawi; Indal Abror (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study analyzes the model of interaction between Islam and science in the Tafsir Ilmi by the Ministry of Religious Affairs of the Republic of Indonesia through Agus Purwanto's typological framework, which categorizes the relationship into the Islamization of Science, the Scientification of Islam, and Islamic Science. Using a literature study method with a descriptive-analytical approach, the results of the study indicate that the Tafsir Ilmi by the Ministry of Religious Affairs of the Republic of Indonesia predominantly applies the model of Islamic Scientification, in which the verses of the Qur'an are positioned as a priori truths that are then verified using modern scientific facts. This finding is concretely identified through the explanation of physiological phenomena in the story of the Companions of the Cave and the role of soil elements in human creation, which are correlated with biochemical data to legitimize the narrative of the sacred text. Although this approach successfully proves the relevance of the Qur'an to the development of science, its apologetic-defensive nature and focus on compatibility are considered less productive for the development of an independent scientific paradigm because science only functions as an instrument supporting the truth of revelation. Consequently, this study recommends the need for further comparative and ethnographic studies to comprehensively understand the integration of religious authority and science in state-sponsored tafsir.